Comparative analysis of 18 chloroplast genomes reveals genomic diversity and evolutionary dynamics in subtribe Malaxidinae (Orchidaceae) - Li, Lin; Yang, Wenting; Liu, Qiang; Jiang, Xingyou; Wu, Kunlin; Fang, Lin; Li, Mingzhi; Zeng, Songjun; Li, Shijin (BMC plant biology, 2025)
The subtribe Malaxidinae encompasses diverse species, many of which possess remarkable medicinal properties that have been employed in traditional Chinese medicine for centuries. Although recent advancements have improved our understanding of the backbone phylogeny of Malaxidinae, clarifying the complex intergeneric relationships remains challenging, largely owing to limited genomic data. To address this gap and further investigate the genetic diversity and evolutionary patterns within this subtribe, we sequenced and assembled complete chloroplast (cp.) genomes from sixteen Malaxidinae species. These newly acquired genomic resources, combined with two previously published cp. genomes from closely related species, were incorporated into a comprehensive comparative genomic and phylogenomic analysis. The complete cp. genomes of all 18 Malaxidinae species were analyzed, revealing lengths ranging from 143,062 bp to 158,785 bp. Each genome contains 123-133 genes, including 74-86 protein-coding genes, 38 tRNA genes, 8 rRNA genes and 1-8 pseudogenes. The chloroplast genomes of Malaxidinae species exhibit significant structural diversity, with particularly pronounced variations observed in the ndhF and ycf1 genes located at the IR/SSC boundary regions. In certain species, the SSC regions showed substantial size reduction, ranging from 10,224 to 15,582 bp. Notable variability in both gene loss and truncation patterns was observed in the ndh gene family across these species, accompanied by diverse modifications affecting the length, position, and pseudogenization of the ycf1 gene. Furthermore, our study identified genomic inversions and rearrangements occurring in both the LSC and SSC regions of specific species. The detection of abundant long dispersed repeats and SSRs provides valuable molecular markers for evaluating both intrageneric and interspecific polymorphism as well as genetic diversity patterns. Through codon usage bias analysis, we established that natural selection serves as the predominant evolutionary force shaping codon usage patterns in most Malaxidinae species. Detailed sequence alignment of the chloroplast genome revealed that structural variants are primarily concentrated within single-copy regions. Ten highly variable cpDNA markers were chosen as mutational hotspots, with the potential for development as DNA barcodes for Malaxidinae species. Our phylogenomic analysis clearly resolved the Malaxidinae into three well-supported major clades. Clade I comprises species of Liparis s.s., Malaxis, and Oberonioides. Clade II includes species of Crepidium, Dienia, Diteilis and Empusa. Clade III consists of species from the genera Blepharoglossum, Cestichis, Oberonia, Platystyliparis and Stichorkis. This research provides valuable insights into the unique characteristics of the chloroplast genome in Malaxidinae orchids, significantly advancing our comprehension of their evolutionary mechanisms and phylogenetic architecture. The acquired genomic data establish a crucial foundation to advance medical resources and aid in species differentiation.